PS02.171: STUDY OF LONG TERM FOLLOW-UP OF EXERCISE LEVELS FOLLOWING PARTICIPATION IN A PREHABILITATION PROGRAMME IN OESOPHAGO-GASTRIC (OG) CANCER SURGERY. (14th September 2018) - Doganay, Emre; Mckinnon, Tom; Osborn, Hayley; Winter-Blyth, Venetia; Moorthy, Krishna
Abstract: Background: Sedentary behaviour is emerging as an important field of scientific enquiry for cancer survivorship research. The aim of this study is to evaluate the impact of PREPARE, a multi-modal pre-operative optimization programme, and the impact this has on sustained activity following completion of cancer treatment. Methods: 66 patients were approached in clinic or sent letters to consent for the study. Median follow up time was 14 months. Patients either consented to telephone questionnaire or exercise testing or both. Telephone questionnaire included the validated Godin-Shephard Leisure-Time physical activity questionnaire in oncology, and exercise testing included the validated Chester-Step test, to obtain an accurate METS score. Scores were calculated at baseline (P1), 6–8 weeks postoperative (P4) and at follow up. Results: 66 patients were included in the study. Of these, 13 (19%) patients were excluded due to disease progression, death or declined to participate. The remaining 43 (65%) who were included in the study either consented for telephone questionnaire (74%) or exercise testing (60%) or both. Median follow up time was 14 months since surgery. Majority of the patients remained active at follow up; 23 (77%) were active, 5 (16%) were moderately active and, 4 (12%) were insufficiently active/sedentary. Overall, the median weekly METS scores were 5.8 (equivalent moderate intensity activity). On exercise testing, there was an improvement in median METS scores. At P1, baseline median METS were 5.0, at P4 5.0 and at 14 months 6.5. There was an overall increase in median self-efficacy scores. At P1, baseline scores were 8.3, at P4 8.5 and at 14 months 9. Conclusion: There is emerging evidence to support the benefits of physical activity in cancer survivors and the impact this has on overall survival, quality of life and symptomatology. Starting prehabilitation at the time of diagnosis leads to improved confidence and sustained activity levels in the post-treatment period. Disclosure: All authors have declared no conflicts of interest.